2020
DOI: 10.37427/botcro-2020-007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of drying on bioactive compounds of blue honeysuckle berries (Lonicera caerulea var. edulis Turcz. ex Herder)

Abstract: Drying fruit is one of the simplest ways to extend the shelf-life of fruit, especially berries. Both higher temperature and time of heating significantly change the contents of some primary and secondary metabolites in honeysuckle fruit. Differences in their contents arising from different heat treatments were determined with the aid of high-performance liquid chromatography (HPLC) coupled with mass spectrophotometry (MS). The content of sugars showed a small change with drying, while organic acid contents dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…The content of polyphenolic substances in fresh blue honeysuckle fruits ranged from 5,370 mg/100 g of dry matter (ʻKarinaʼ variety) to 7,336 mg/100 g of dry matter (ʻBoreal Blizzardʼ). According to L. Shevchuk et al (2022), the variation in the content of polyphenolic substances in blue honeysuckle is quite high, with a coefficient of variation of 22%, as also evidenced by studies by M. Senica et al (2020). At the level of 6,900 and 6,387 mg/100 g of dry matter, they were accumulated by the fruits of ʻBoreal Bistʼ and ʻBoreal Beautyʼ, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…The content of polyphenolic substances in fresh blue honeysuckle fruits ranged from 5,370 mg/100 g of dry matter (ʻKarinaʼ variety) to 7,336 mg/100 g of dry matter (ʻBoreal Blizzardʼ). According to L. Shevchuk et al (2022), the variation in the content of polyphenolic substances in blue honeysuckle is quite high, with a coefficient of variation of 22%, as also evidenced by studies by M. Senica et al (2020). At the level of 6,900 and 6,387 mg/100 g of dry matter, they were accumulated by the fruits of ʻBoreal Bistʼ and ʻBoreal Beautyʼ, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…ese explain the fact that not all techniques are appropriate for the extraction of certain compounds. Studies have shown that thermo-labile components decompose or become unstable at high temperatures [265,266]. Flavanol and anthocyanins, for example, are affected by high temperatures [265].…”
Section: Poor Ermal Stabilitymentioning
confidence: 99%
“…Studies have shown that thermo-labile components decompose or become unstable at high temperatures [265,266]. Flavanol and anthocyanins, for example, are affected by high temperatures [265]. Consequently, green techniques such as ultrasonic-assisted extraction, pressurized liquid extraction, natural deep eutectic solvent, and supercritical fluid extraction are suitable for extracting alkaloids, phenolic compounds, flavonoids, essential oils, terpenoids, saponins, and lipids in high yield [266][267][268][269][270].…”
Section: Poor Ermal Stabilitymentioning
confidence: 99%
“…Blue honeysuckle fruit is rich in phenolic compounds, vitamins, and acids. Moreover, it is known to contain magnesium, calcium, potassium, and phosphorus [ 23 ]. Blue honeysuckle is also rich in polyphenols, i.e., secondary plant metabolites with highly diverse chemical structures.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, blue honeysuckle berries contain from 30.5 to 186.6 mg of ascorbic acid. A slightly different range is reported by Szot et al [ 24 ], who assert that it varies from 48.4 to 66.1 mg/100 g. It is also worth highlighting that blue honeysuckle berries contain B vitamins: thiamine (vitamin B1), riboflavin (vitamin B2), pantothenic acid (vitamin B5), pyridoxine (vitamin B6), folic acid (vitamin B9), as well as nicotinamide (vitamin PP), biotin (vitamin H), and p-aminobenzoic acid (PABA) [ 16 , 20 , 21 , 22 , 23 ]. Vitamins of this group are increasingly used in the formulation of cosmetics because of their favorable impact on the condition of the skin.…”
Section: Introductionmentioning
confidence: 99%